RESULTS OF DEVELOPMENT AND RESEARCH OF THE TECHNOLOGY FOR AUTOMATED ENERGY-EFFICIENT CONTROL OF HEAT PUMP SYSTEMS BY MEANS OF COMPUTER EXPERIMENT - OLISHEVSKYI, ILLIA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The development of energy-efficient indoor management systems, involving the current engineering and technical solutions to control and optimize energy consumption, is both relevant and promising area. This allows addressing the issues of saving energy resources; improving energy efficiency; and strengthening energy independence. The use of geothermal heat pumps and air conditioning systems with heat utilization are the advanced areas for the development of energy-efficient technologies in the construction sector. The paper concerns the study of technical-functional and energy characteristics, and parameters of a residential building heat supply system with integrated automated control means by synthesizing computer-oriented and computer-integrated models of heating and air conditioning systems using a geothermal heat pump and a thermal accumulator which will increase the energy efficiency of the building and optimize the use of thermal energy throughout the year. The object of study is the processes of accumulation, distribution and utilization of thermal energy in heating and air conditioning systems. The subject of the study is computer-aided models of indoor heat supply including a geothermal heat pump, a thermal accumulator and a radiator heating system as well as an air conditioning system with the possibility of heat utilization. The main scientific and practical effect of the obtained results is the development of computer-oriented models of indoor heating and air conditioning systems which, unlike the previously known ones, implement adaptive heat utilization to the heat accumulator for hot water supply needs. Further promising research in the areas will expand and deepen the scientific substantiation of software and hardware solutions aimed at improving the energy efficiency of heat engineering industrial and household facilities and processes.
Keywords: heat utilization; heat pump; conditioning; computer-aided model